Studi kapasitas masyarakat sebagai mekanisme bertahan menghadapi bencana banjir di Desa Sitiarjo, Kecamatan Sumbermanjing Wetan, Kabupaten Malang - Mohamad Mambaus Su'ud; Mashur Hasan Bisri (Universitas Negeri Malang, 2019)
The aim of this study was to determine the capacity of communities as a mechanism to withstand floods Sitiarjo Village, District Sumbermanjing Wetan. This research is descriptive qualitative. The research phase was divided into three, i.e: (1) pre-field observation; (2) field observation; (3) data processing. The method used in data collection is FGD (Focused Group Disscusion) and in-depth interviews. The results of the study indicate that the community has a strong capacity in social, cultural, economic and government aspects in dealing with floods. In the socio-cultural aspect, the community develops a local early warning system through